HIV seroprevalence among male IVDUs in Houston, Texas. - Williams, M L (1990)
HIV seroprevalence was 8.4 percent in a sample of 921 heterosexual male intravenous drug users in Houston, Texas who were not in drug treatment at the time of the study. Males who were Black, injected drugs daily, or had a history of syphilis had greater odds of being HIV positive than participants without those characteristics.